ANALISIS PERTUMBUHAN LABA PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK DI BEI - Nadhila Putri Ghaisani; Nurjanti Takarini (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Financial statements are used to find sources of company financial information that aims to analyze the financial performance of a company. Financial ratios are a tool to see profit growth. This study prioritizes the function of financial ratios to the company's profit growth. This research was conducted with the aim of knowing whether or not there is an influence of financial ratios, namely the ratio of liquidity, solvency and activity on the profit growth of companies in the transportation and logistics sector listed on the Indonesia Stock Exchange (IDX). This study used 28 populations. The sample selection used a non-probability sampling technique with purposive sampling type was found to find 19 samples of transportation and logistics companies for the period 2018-2021. Testing the data used consisted of classical assumption and multiple linear regression analysis. The observation results show is that partially the liquidity and solvency variables affect the company's profit growth with a significant negative, while the activity variable affects the company's profit growth with a significant positive. The results of the observation show that the liquidity, solvency and activity variables simultaneously influence the company's profit growth significantly.